2010 IEEE International Power Modulator and High Voltage Conference 2010
DOI: 10.1109/ipmhvc.2010.5958442
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime tests on a high ohms/square metalized high crystalline polypropylene film capacitor with application to a Marx modulator

Abstract: Abstract-This paper presents accelerated lifetime tests on a polypropylene film capacitor. Experimental parameters (20% droop, 5 Hz repetition rate) simulate anticipated operating conditions encountered in the SLAC P2 Marx. Elevated film electric field stress is utilized as the acceleration parameter. Results indicate that, for the particular film of interest, a film stress of ~290 V/µm corresponds to a 10 5 hour lifetime. In addition, the voltage scaling exponent for this film is 13.1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…An initial study was conducted on the polypropylene film chosen for the cell [13]. Although it has been shown that many factors affect aging in self-healing capacitors (temperature, reverse voltage magnitude, reverse voltage frequency, etc.)…”
Section: Energy Storagementioning
confidence: 99%
“…An initial study was conducted on the polypropylene film chosen for the cell [13]. Although it has been shown that many factors affect aging in self-healing capacitors (temperature, reverse voltage magnitude, reverse voltage frequency, etc.)…”
Section: Energy Storagementioning
confidence: 99%